Praying for salvation: a map of relatedness. Issue 1 (2nd January 2017) - Webster, Joseph
Abstract : This article attempts to push Mauss' work on the sociality of prayer (1909) to its fullest conclusion by arguing that prayer can be viewed anthropologically as providing a map for social and emotional relatedness. Based on fieldwork among deep-sea fisher families living in Gamrie, North-East Scotland (home to 700 people and six Protestant churches), the author takes as his primary ethnographic departure the ritual of the 'mid-week prayer meeting'. Among the self-proclaimed 'fundamentalists' of Gamrie's Brethren and Presbyterian churches, attending the prayer meeting means praying for salvation. Yet, contrary to the stereotype of Protestant soteriology as highly individualist, in the context of Gamrie, salvation is not principally focused upon the self, but is instead sought on behalf of the 'unconverted' other. Locally, this 'other' is made sense of with reference to three different categories of relatedness: the family, the village and the nation. The author's argument is that each category of relatedness carries with it a different affective quality: anguish for one's family, resentment toward one's village, and resignation towards one's nation. As such, prayers for salvation establish and maintain not only vertical – human-divine – relatedness, but also horizontal relatedness between persons, while also giving them their emotional tenor. In 'fundamentalist' Gamrie, these human relationships, and crucially their affective asymmetries, may be mapped, therefore, by treating prayers as social phenomena that seek to engage with a world dichotomised into vice and virtue, rebellion and submission, and, ultimately, damnation and salvation.